Bodies. Between Space and Design. - Bianchetti, Cristina (Jovis, 2020)
The European tradition of urbanism has two main lines. The more influential of these clearly addresses the “place” as the limit of architectural and urban design. We cannot conceive of life without profound roots in places. The other traditional line in urbanism gravitates around the “body”. Although not as influential, it suggests a different approach to modern urbanism. The perspective developed here questions what happens in-between the “body” and “space”. To do this, the “body” is understood as a transit channel between space and the urban project. The book unfolds a critical reading of contemporary architectural design and urbanism and criticises the way design refers to “space” using the “body”. In doing so, it delves into the debates of architecture and urban planning of the eighties, as well as their ambiguous relationship with politics.

Die europäische Geistesgeschichte gliedert sich im Urbanismus in zwei große Traditionslinien. Die einflussreichere geht vor allem vom Raum als Grenze zwischen architektonischer und urbaner Gestaltung aus. Ihr zufolge ist ein Leben ohne Ortsgebundenheit nicht möglich. Die andere nimmt den Körper als Ausgangspunkt und sieht in ihm ein Medium zwischen Raum und Urbanität. Cristina Bianchetti entfaltet mithilfe des Körper-Konzepts eine historisch-kritische Lesart zeitgenössischer Positionen in Architektur und Urbanismus. Dabei taucht sie tief in die wissenschaftlichen und politischen Diskussionen der Architektur und des Urbanismus der 1980er Jahre ein.
Keywords: Urbanismus; Stadtraum; Raumbezogenheit; Ortsbezogenheit; Körper; Leben; Architekturphilosophie; Raumtheorie; Stadttheorie; Stadtsoziologie